Modeling thermoelectric power generation in view of climate change - Förster, Hannah; Lilliestam, Johan (Regional Environmental Change, 2010)
In this study we investigate how thermal power plants with once-through cooling could be affected by future climate change impacts on river water temperatures and stream flow. We introduce a model of a steam turbine power plant with once-through cooling at a river site and simulate how its production could be constrained in scenarios ranging from a one degree to a five degree increase of river temperature and a 10-50% decrease of stream flow. We apply the model to simulate a large nuclear power plant in Central Europe. We calculate annual average load reductions, which can be up to 11. 8%, assuming unchanged stream flow, which leads to average annual income losses of up to 80 million €. Considering simultaneous changes in stream flow will exacerbate the problem and may increase average annual costs to 111 million € in a worst-case scenario. The model demonstrates that power generation could be severely constrained by typical climate impacts, such as increasing river temperatures and decreasing stream flow. © 2009 Springer-Verlag.
CRIS-Team Scopus Importer:2023-06-14
Keywords: Climate change; Cooling; Nuclear power; Thermoelectric power; Water demand